In vitro antagonistic inhibitory effects of palm seed crude oils and their main constituent, lauric acid, with oxacillin in Staphylococcus aureus - Lalouckova, Klara; Skrivanova, Eva; Rondevaldova, Johana; Frankova, Adela; Soukup, Josef; Kokoska, Ladislav (Scientific reports, 2021)
Infections caused by Staphylococcus aureus are a serious global threat, and with the emergence of antibiotic resistance, even more difficult to treat. One of the possible complications in antistaphylococcal therapy represents negative interactions of antibiotics with food. In this study, the in vitro interaction between oxacillin and crude palm seed oil from Astrocaryum vulgare, Cocos nucifera, and Elaeis guineensis against nine strains of S. aureus was determined using the checkerboard method. Lauric acid was identified as a major constituent of all tested oils by gas chromatography. The results showed strong concentration dependent antagonistic interactions between palm oils and oxacillin with values of fractional inhibitory concentrations indices ranging from 4.02 to 8.56 at concentrations equal or higher than 1024 µg/mL of the tested oils. Similarly, lauric acid in combination with oxacillin produced antagonistic action with fractional inhibitory concentration indices ranging from 4.01 to 4.28 at 1024 µg/mL. These findings suggest that interference between oxacillin and palm oils and their constituents can negatively affect the treatment of staphylococcal infections in humans and other animals.
Keywords: Drug Antagonism; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; kyseliny laurové; oxacilin; Lauric Acids; Anti-Bacterial Agents; ropa; mikrobiální testy citlivosti; Microbial Sensitivity Tests; Oxacillin; antagonismus léků; Staphylococcus aureus; antibakteriální látky; Petroleum